Zmniejszenie pooperacyjnego odczynu zapalnego wskutek zastosowania octanu triamcynolonu podczas witrektomii pars plana - Mańkowska, Anna; Rejdak, Robert; Oleszczuk, Agnieszka; Kiczyńska, Magdalena; Łękawa, Anna; Chorągiewicz, Tomasz; Zagórski, Zbigniew (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To prospectively evaluate the effect on postoperative inflammatory reaction and recovery after application of triamcinolone acetonide (TA) during pars plana vitrectomy (PPV), to visualize the vitreous. Material and methods: Pars plana vitrectomy (PPV) was performed in 45 patients (21 males, 24 females) (29 with retinal detachment, 6 with macular hole, 1 with cystoid macular edema, 3 with diabetic retinopathy, 3 with vitreous haemorrhage, 1 with preretinal membrane, 1 with PVR and 1 with lens luxation). After surgical separation of the posterior vitreous and removal of any visible epiretinal membrane, TA was injected over the posterior pole. For the control group we used 15 patients (10 with retinal detachment, 2 with macular hole, 1 with preretinal membrane, 1 with lens luxation and 1 with vitreous haemorrhage) (10 males, 5 females) treated with PPV but without TA administration. To evaluate the degree of postoperative inflammation and to monitor the dynamics of the blood-aqueous barrier disruption, the laser flare cell meter (Kowa FM-500) was used. Results: Tyndalometric mean values in the control group of eyes recorded 1 day after PPV were 32.41 ± 6.1 ph/ msec while values in TA-treated group were significantly lower (20.26 ± 2.4, p<0.02). 10 days after surgery in TA group results were still significantly lower as compared to the control group (16.4 ± 2.6 vs 32.5 ± 9.6, p<0.005). As observed 6 weeks after PPV, tyndalometric recordings in TA-treated group remained lower as those observed in the control group (16.1 ± 3.1 vs 32.0 ± 8.1, p<0.01). Conclusions: The eyes which received TA-assisted PPV showed significantly less breakdown of the blood–ocular barrier than those with routine PPV. Intraoperative administration TA facilitates postoperative recovery after surgery lowering the inflammatory reaction.